Empowering Tourism Communication for Sustainable Village Development - I Gusti Ngurah Agung Kade Dwi Arsana; Laurens Bethany; Olivia Smith (Pandawan Sejahtera Indonesia, 2024)
The research addresses the critical issue of enhancing tourism communication to foster sustainable village development. The primary objective is to empower local communities by improving their communication strategies, thereby boosting tourism and ensuring sustainable growth. The study employs a mixed-method approach, combining qualitative and quantitative data to comprehensively understand the current communication practices and their impact on tourism. Data were collected through surveys, interviews, and field observations in selected villages known for their tourism potential. The findings reveal significant gaps in the existing communication strategies, highlighting the need for more effective and targeted approaches. The research concludes that by adopting improved communication methods, villages can attract more tourists, enhance their economic stability, and promote sustainable development. The study provides actionable recommendations for local governments and community leaders to implement more effective tourism communication practices, ultimately contributing to the sustainable development of rural areas.